2022
DOI: 10.1186/s10020-022-00486-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced parasympathetic cholinergic activity with galantamine inhibited lipid-induced oxidative stress in obese African Americans

Abstract: Background African Americans (AAs) are disproportionately affected by cardiovascular disease (CVD), they are 20% more likely to die from CVD than whites, chronic exposure to inflammation and oxidative stress contributes to CVD. In previous studies, enhancing parasympathetic cholinergic activity has been shown to decrease inflammation. Considering that AAs have decreased parasympathetic activity compared to whites, we hypothesize that stimulating it with a central acetylcholinesterase (AChE) inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Previous work has shown that African American individuals have a greater oxidative stress response to lipid infusion at doses of 0.8 mL/m 2 /min with heparin (200 U/hrs for 4 hrs) than in Whites (Lopes et al., 2003), which is confirmed by plasma levels of the oxidative stress biomarker F2‐isoprostane (Parsa et al., 2022; Saleem et al., 2023). However, a reliable protocol to measure dynamic changes in oxidative stress responses in human endothelial cells has yet to be developed.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Previous work has shown that African American individuals have a greater oxidative stress response to lipid infusion at doses of 0.8 mL/m 2 /min with heparin (200 U/hrs for 4 hrs) than in Whites (Lopes et al., 2003), which is confirmed by plasma levels of the oxidative stress biomarker F2‐isoprostane (Parsa et al., 2022; Saleem et al., 2023). However, a reliable protocol to measure dynamic changes in oxidative stress responses in human endothelial cells has yet to be developed.…”
Section: Introductionmentioning
confidence: 83%
“…The differences in the results endpoints are insignificant because we are still blinded to the treatment of these participants. Considering that the patients also received galantamine, which diminishes NADPH oxidase activity and lowers oxidative stress levels (Parsa et al., 2022), galantamine may have mitigated the inflammatory and oxidative impact of lipid infusion in the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of F 2 -IsoPs were measured in plasma using negative ion gas chromatographymass spectrometry by the Vanderbilt University Eicosanoid Core Laboratory as previously described [37,38]. Similarly, levels of F 2 -IsoPs in PBMCs were measured as previously described [39].…”
Section: Measurement Of F 2 -Isops In Plasma and Peripheral Blood Mon...mentioning
confidence: 99%